An analysis of postural control strategies in various types of footwear with varying workloads. (4th May 2021) - Chander, Harish; Garner, John C.; Wade, Chip; Wilson, Samuel J.; Turner, Alana J.; Kodithuwakku Arachchige, Sachini N. K.; Hill, Christopher M.; DeBusk, Hunter; Simpson, Jeffrey D.; Miller, Brandon L.; Morris, Cody; Knight, Adam C.
Abstract: Footwear and physiological workload have been reported to impact postural stability. Analyses of postural strategies during sensory organisation test (SOT) can aid better understanding of postural control behaviour. The paper reports previously unreported postural strategy scores from each SOT condition, in various types of footwear when exposed to different workloads from two different completed studies. Study 1 analysed postural strategies in alternative footwear [Crocs (CC), flip-flops (FF) and Vibram five-finger (VIB)] before and after a low-intensity workload ( n  = 18; age: 22.9 ± 2.8 years; height: 179 ± 6.0 cm; mass: 81.3 ± 8.8 kg) and study 2 in military footwear [standard tactical boot (STD) and minimalist tactical boot (MIN)] before and after a high-intensity workload ( n  = 16; age: 26.63 ± 3.93 years; height: 178.04 ± 6.2 cm; mass: 87 ± 12.4 kg). Findings from the current analyses revealed significant differences in footwear type, workload, and SOT conditions. Design characteristics on alternative footwear and the low intensity workload were not sufficient to cause a significant shift from a predominant ankle to hip strategy. However, design characteristics of STD and the high-intensity workload did cause a shift from an ankle to hip strategy. During SOT conditions where all three types of feedback was readily available (visual, vestibular and somatosensory), an ankle strategy was used to maintain postural stability, while more reliance on hip strategy existed when sensory feedback was absent or in conflict.